Strategies for Improving Food Security in Remote and Outermost Island Areas - Levianto, Jubei; Kusuma, Airlangga Surya; Warsidi, Warsidi (Borong Newinera Publisher, 2026)
Food security in remote and outermost islands is an increasingly urgent strategic issue in the context of sustainable development in Indonesia. This study aims to analyze the challenges, strategies, and policy implications of food security in these regions using a literature review method. A total of 21 scholarly articles and policy documents (2021–2025) were critically reviewed based on the FAO’s five-pillar framework: availability, access, utilization, stability, and sustainability/agency. Findings reveal that limited local production, high food distribution costs, dietary shifts from traditional foods to low-nutrition imports, climate vulnerability, and low community participation are the main drivers of food insecurity. The latest FSVA 2025 data indicates national improvement, with food-vulnerable areas reduced from 92 districts (2024) to 81 (2025). The Food Security Index (IKP 2024) also highlights persistent vulnerability pockets, particularly in small and outermost islands. In response, the National Food Agency (NFA) has strengthened the Diverse, Nutritious, Balanced, and Safe Food Program (B2SA) in 809 locations and accelerated the implementation of the Free Nutritious Meal (MBG) program in 3T areas such as Morotai and Nias Selatan. These initiatives prioritize the use of local food resources (fish, maize, horticultural products) and the establishment of MBG kitchens that comply with nutrition and food safety standards. The most relevant strategies for the Indonesian context include local food diversification (sago, maize, cassava, fish, moringa), agroforestry, blue food governance, strengthening local institutions, and integrating national programs such as the sea toll and MBG